Lessons learned from a design-based research implementation: a researcher’s methodological account - Parmaxi, Antigoni; Zaphiris, Panayiotis (My University, 2020)
This paper describes aspirations and contributions that grew out of a developmental cycle of design-based research (DBR) implementation conducted over a three-year project. DBR engineers new learning environments and improves learning in context whilst communicating usable knowledge for learning and teaching in complex settings. This project employed constructionism as an overarching framework, a theory of learning, teaching, and design, which supports that learning occurs more effectively when learners understand the world around them by creating meaningful artifacts that can be probed and shared. In an attempt to infuse elements of constructionism in the use of social technologies, groups of learners were assigned to construct an artifact within social technologies. The main data collection tools employed were students’ and instructor’s reflections, a questionnaire, semi-structured interviews and observation of groups’ activity within social technologies. Such an inquiry revealed both strengths and challenges with regard to implementing DBR and reporting how designs function in real-life settings. This paper brings forward considerations related to reporting intentionally designed interventions, potentials and limitations of DBR and implications for future DBR implementations.
Keywords: Design-based research; Constructionism; Artifacts; Social media; Social technologies; Language classroom